Pulmonary Circulation Transvascular Fluid Fluxes Do Not Change during General Anesthesia in Dogs - Frlic, Olga; Seliškar, Alenka; Domanjko Petrič, Aleksandra; Blagus, Rok; Heigenhauser, George; Vengust, Modest (Frontiers in Physiology, 2018)
General anaesthesia (GA) can cause abnormal lung fluid redistribution. Pulmonary circulation transvascular fluid fluxes (JVA) are attributed to changes in hydrostatic forces and erythrocyte volume (EV) regulation. Despite the very low hydraulic conductance of pulmonary microvasculature it is possible that GA may affect hydrostatic forces through changes in pulmonary vascular resistance, and EV through alteration of erythrocyte transmembrane ion fluxes (ionJVA). Furosemide (Fur) was also used because of its potential to affect pulmonary hydrostatic forces and ionJVA. A hypothesis was tested that JVA, with or without furosemide treatment, will not change with time during GA. Twenty dogs that underwent castration/ovariectomy were randomly assigned to Fur (n=10) (4 mg/kg IV) or placebo treated group (Con, n=10). Baseline arterial (BL) and mixed venous blood were sampled during GA just before treatment with Fur or placebo and then at 15, 30 and 45 min post-treatment. Cardiac output (Q) and pulmonary artery pressure (PAP) were measured. JVA and ionJVA were calculated from changes in plasma protein, hemoglobin, hematocrit, plasma and whole blood ions, and Q. Variables were analyzed using random intercept mixed model (P<0.05). Data are expressed as means ±SE. Furosemide caused a significant volume depletion as evident from changes in plasma protein and hematocrit (P<0.001). However; Q, PAP and JVA were not affected by time or Fur, whereas erythrocyte fluid flux was affected by Fur (P=0.03). Furosemide also affected erythrocyte transmembrane K+ and Cl-, and transvascular Cl- metabolism (P≤0.05). No other erythrocyte transmembrane or transvascular ion fluxes were affected by time of GA or Fur. Our hypothesis was verified as JVA was not affected by GA or ion metabolism changes due to Fur treatment. Furosemide and 45 min of GA did not cause significant hydrostatic changes based on Q and PAP. Inhibition of Na+/K+/2Cl- cotransport caused by Fur treatment, which can alter EV regulation and JVA, was offset by the Jacobs Stewart cycle. The results of this study indicate that the Jacobs Stewart cycle/erythrocyte Cl- metabolism can also act as a safety factor for the stability of lung fluid redistribution preserving optimal diffusion distance across the blood gas barrier.